The Climax Prophecy Studies on the Book of Revelation - Bauckham, Richard (Edinburgh ; New York T&T Clark Ltd., 1993)
The Apocalypse of John is a work of immense importance and learning. Yet among the major works of early Christianity included in the New Testament it has received relatively little scholarly attention. This work is a significant contribution to remedying
Keywords: Bible. -- Revelation -- Criticism, interpretation, etc. Bible. -- Revelation. Bible. -- New Testament. -- Apocalypse -- Critique, interprétation, etc